Uncovering The Secrets of Smart Investors: How Knowledge, Attitudes And Understanding of Taxes Drive Investment Decisions In The Bibit Malang Raya Application - Nova Kartika Sari; Jeni Susyanti; Nurhidayah (Faculty of Economics, Merdeka University Surabaya, Indonesia, 2024)
Globalization and new lifestyles encourage investment as a smart financial solution. BIBIT, a popular platform, needs to improve its profitability. This research shows that financial knowledge and attitudes, tax knowledge, and locus of control are important for wise investment decisions. This research uses an associative quantitative design with primary data from 170 Bibit investors in Malang Raya. Data were analyzed using multiple linear regression and mediation path analysis to test the relationship between variables. Classical assumptions are tested and the model is evaluated with SmartPLS. The majority of BIBIT users (86%) like the way the platform avoids inflation. Users also agree (95%) that BIBIT considers profit and loss and annual profits in selecting and managing mutual fund investments. This shows user satisfaction with BIBIT's ability to protect the value of money and maximize profits. Financial knowledge and attitudes, as well as tax knowledge, significantly influence the investment decisions of BIBIT investors in Malang Raya. Financial attitudes and knowledge also influence locus of control, but tax knowledge does not. Financial knowledge and attitudes, mediated by locus of control, positively influence investment decisions.